Assessing the impact of community-based tourism: an integrated framework for sustainable development - Liu, Lisha; Abdullah, Nawal Hanim; Binti Raja Yusof, Raja Nerina; Ramachandran, Sridar (Human Resources Management Academic Research Society (HRMARS), 2024)
This study proposes an integrated framework for assessing the impact of community-based tourism (CBT) on sustainable development. The framework combines elements of community participation, economic viability, and environmental sustainability to provide a comprehensive evaluation of CBT initiatives. The research aims to bridge the gap between theoretical models and practical applications in the field of sustainable tourism.